Substance P Increases Cell-Surface Expression of CD74 (Receptor for Macrophage Migration Inhibitory Factor): In Vivo Biotinylation of Urothelial Cell-Surface Proteins - Katherine L. Meyer-Siegler; Shen-Ling Xia; Pedro L. Vera (Mediators of Inflammation)
Macrophage migration inhibitory factor (MIF), an inflammatory cytokine, and its receptor CD74 are upregulated by bladder inflammation. MIF-mediated signal transduction involves binding to cell-surface CD74, this study documents, in vivo, MIF-CD74 interactions at the urothelial cell surface. N-hydroxysulfosuccinimide biotin ester-labeled surface urothelial proteins in rats treated either with saline or substance P (SP, 40 μg/kg). The bladder was examined by histology and confocal microscopy. Biotinylated proteins were purified by avidin agarose, immunoprecipitated with anti-MIF or anti-CD74 antibodies, and detected with strepavidin-HRP. Only superficial urothelial cells were biotinylated. These cells contained a biotinylated MIF/CD74 cell-surface complex that was increased in SP-treated animals. SP treatment increased MIF and CD74 mRNA in urothelial cells. Our data indicate that intraluminal MIF, released from urothelial cells as a consequence of SP treatment, interacts with urothelial cell-surface CD74. These results document that our previously described MIF-CD74 interaction occurs at the urothelial cell surface.